The The Impact of Accounting Knowledge, Perceptions, and Job Market Factors on Students Career Interest as Public Accountants - Hali, Antonyo Almase Gasi; Candra, Yudas Tadius Andi (Manunggal Halim Jaya, 2025)
Public accountant is a profession that has an official license to operate independently as a private accountant and offer professional services. The public accountant profession offers professional services to audit an agency or company's financial statements. The purpose of this study was to determine the effect of the level of understanding of accounting, student perceptions, and labor market analysis on the preferences of accounting students at Mercu Buana University Yogyakarta to work as public accountants. With the research tool used in this research, namely the multiple linear regression analysis method. The population in this study were accounting students at Mercu Buana University Yogyakarta Class of 2021, in this study the purposive sampling method was used to determine the sample and then clarified using the Slovin formula. The results of the study indicate that students' interest in a career as a public accountant is not influenced by their understanding of accounting. In contrast, student perceptions and labor market considerations affect their interest in a career as a public accountant.